2023
DOI: 10.3389/fmicb.2022.1082025
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA EN-90756 promotes CPB2-induced proliferation and inhibits apoptosis in IPEC-J2 cells by affecting the JAK-STAT signaling pathway activation

Abstract: BackgroundLong non-coding RNAs (lncRNAs), as key regulators, are closely associated with the development of a variety of disease. However, the mechanisms by which lncRNAs regulate Clostridium perfringens type C induced piglet diarrhea are unclear.MethodsIn the present study, we explored the expression and characterization of lncRNAs in a C. perfringens beta2 (CPB2) toxin-treated intestinal porcine epithelial cell line-J2 (IPEC-J2) using RNA-sequencing (RNA-seq).ResultsA total of 6,558 lncRNAs were identified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Similarly, lncRNA EN-90756 regulates CPB2-induced proliferation and apoptosis in IPEC-J2 cells by affecting the JAK–STAT signaling pathway. In addition, it impacts cellular antiviral capacity by modulating the protein level of MX1 [ 28 ]. Previous MeRIP-sequencing studies revealed that m6A-modified lncRNA EN_42575 was significantly altered in CPB2-group cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, lncRNA EN-90756 regulates CPB2-induced proliferation and apoptosis in IPEC-J2 cells by affecting the JAK–STAT signaling pathway. In addition, it impacts cellular antiviral capacity by modulating the protein level of MX1 [ 28 ]. Previous MeRIP-sequencing studies revealed that m6A-modified lncRNA EN_42575 was significantly altered in CPB2-group cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%